Sintesis ferrat dari Fe(NO3)3 dan NaOCl sebagai pendegradasi zat pewarna makanan tartrazine - Eldat Wira Santa; La Baru Moses (Jurnal Kimia Fullerene, 2018)
This investigation was carried out in order to synthesize ferrate (FeO42-) and was applied to the degradation of the food coloring agent of tartrazine. The synthesis of ferrate is carried out by the reaction of Fe(NO3)3 and NaOCl as oxidants in alkaline conditions. The synthesis was monitored using a UV-Vis spectrophotometer and resulted in a wavelength of 510 nm. The resulting ferrate is crystallized using KCl. The resulting crystals are potassium ferrate of 0.977 g. The angle of potassium ferrate 2q is measured with X-ray diffraction (XRD), which produces an angle of 2q of 28,480. Potassium ferrate was applied to degrade the tartrazine dye that was controlled using the UV-Vis spectrophotometer. The effect of several parameters on the tartrazine dye that degrades the reaction, such as the pH and the molar ratio of ferrate and tartrazine, was also studied in this study. The results showed that ferrate can degrade tartrazine at pH 9.6 with the highest degradation present in the molar ratio of ferrate and tartrazine 1: 5 which is 98.45%. This suggests that ferrate are an alternative and environmentally friendly substance that can be used to degrade tartrazine dye.